FRI0403 How early starts increased collagen synthesis in systemic sclerosis?. (23rd January 2014) - Ingegnoli, F.; Gualtierotti, R.; Schioppo, T.; Orenti, A.; Boracchi, P.; Lubatti, C.; Murgo, A.; Zeni, S.; Mastaglio, C.; Galbiati, V.; Monti, G.; Grossi, C.; et al.
Abstract : Background: One of the hallmarks of overt Systemic Sclerosis (SSc) is the interstitial and perivascular fibrosis resulting in functional impairment of affected organs. During the fibrotic process, the increased collagen synthesis has been correlated to the increase of some biomarkers of collagen metabolism, but it is not know how early these biomarkers can be detected during the disease course. Objectives: To evaluate the ongoing fibrotic process based on collagen biomarkers in a cohort of patients in different phases of the disease: from isolated Raynaud's phenomenon (RP) to overt SSc. For this purpose tissue inhibitor of matrix metalloproteinases-1 (TIMP-1), hyaluronic acid (HA), aminoterminal propeptide of type III procollagen (PIIINP) and Enhanced Liver Fibrosis (ELF) test were chosen. Methods: 140 consecutive adult subjects referring in approximately 6 months time were enrolled. They were classified as: 1) primary RP (pRP) [1 ]; 2) RP suspected secondary to SSc; 3) very early SSc [2 ]; 4) limited cutaneous (lc)-SSc; and 5) diffuse cutaneous (dc)-SSc. Patients with any other fibrosing disorder or treated with interferon were excluded. TIMP-1, HA, PIIINP and ELF score (derived from an algorithm of the above mentioned biomarkers) were blindly determined by an independent commercial service (iQur, UK). Statistical analysis was performed by regression modelling and ROC curve analysis adjusting for age. Results: The study population consisted in 50 pRP (47 women, median age 44.5 yrs), 43 RP suspected secondary to SSc (43 women, median age 43 yrs), 16 very early SSc (16 women, median age 57.5 yrs), 15 lc-SSc (14 women, median age 67 yrs), and 15 dc-SSc (13 women, median age 65 yrs). 1 patient was excluded for a recent treatment with interferon. The ELF test and HA were significantly higher in patients with very early SSc compared to subjects with RP suspected secondary to SSc (ELF test: median 8, 46 vs 7, 84 ng/ml, p= 0.0286; HA: median 30, 62 vs 13, 6 ng/ml, p= 0.03). PIIINP was significantly higher in patients with dc-SSc compared to very early SSc (median 7, 23 vs 5, 42 ng/ml; p= 0.006). These differences were not confirmed when these results were weighted for age. When patients with overt SSc were studied an increase of these biomarkers was observed as a trend, but only PIIINP reached a statistical significance. This last result was also confirmed once being weighed for age. Conclusions: In our study, the selected biomarkers were not able to distinguish among subjects between pRP, suspected secondary RP, and patients with very early SSc. Nevertheless, these fibrosis biomarkers showed an increasing trend in different subgroups and with age, with no relation to RP duration. These data support the hypothesis that the immune perturbations and vascular injury precede the development of fibrosis, which, in turn, further exacerbates vascular and immune damage. References: LeRoy EC, Medsger TA, Jr. Clin Exp Rheumatol. 1992;10:485-8. Avouac J, Fransen J, Walker UA, Riccieri V, Smith V, Muller C, et al. Ann Rheum Dis. 2011;70:476-81. Disclosure of Interest: None Declared